TP63 Transcripts Play Opposite Roles in Chicken Skeletal Muscle Differentiation - Luo, Wen; Ren, Xueyi; Chen, Jiahui; Li, Limin; Lu, Shiyi; Chen, Tian; Nie, Qinghua; Zhang, Xiquan (Frontiers in Physiology, 2018)
Tumour protein 63 (TP63) comprises multiple isoforms and plays an important role during embryonic development. It has been shown that TP63 knockdown inhibits myogenic differentiation, but which isoform is involved in the underlying myogenic regulation remains uncertain. Here, we found that two transcripts of TP63, namely, TAp63α and ΔNp63α, are expressed in chicken skeletal muscle. These two transcripts have distinct expression patterns and opposite functions in skeletal muscle development. TAp63 has higher expression in skeletal muscle than in other tissues, and its expression is gradually upregulated during chicken primary myoblast differentiation. ΔNp63 can be expressed in multiple tissues and exhibits stable expression during myoblast differentiation. TAp63α overexpression inhibits myoblast proliferation, induces cell cycle arrest, and enhances myoblast differentiation. However, although ΔNp63α has no significant effect on cell proliferation, the overexpression of ΔNp63α inhibits myoblast differentiation. Using isoform-specific overexpression assays following RNA-sequencing, we identified potential downstream genes of TAp63α and ΔNp63α in myoblast. Bioinformatics analyses and experimental verification results showed that the differentially expressed genes (DEGs) between the TAp63α and control groups were enriched in the cell cycle pathway, whereas the DEGs between the ΔNp63α and control groups were enriched in muscle system process, muscle contraction, and myopathy. These findings provide new insights into the function and expression of TP63 during skeletal muscle development, and indicate that one gene may play two opposite roles during a single cellular process.